Reflections on Rasāyana, Bcud Len and Related Practices in Nyingma (Rnying Ma) Tantric Ritual - Cantwell, Cathy (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
The Tibetan term, bcud len, "imbibing the essence juice", is considered an equivalent for the Sanskrit term, rasāyana. But in Tibetan Buddhist ritual manuals, both terms occur, apparently with slightly different connotations. Practices classified as bcud len are frequently relatively short, and seem primarily designed for the use of individual yogis, usually as a subsidiary practice to complement their main tantric meditation. The production of bcud len pills which are said to sustain, rejuvenate and extend the life of the body, or even to bring immortality, is often an integral part of the practice. The term, rasāyana, is used in Tibetan transliteration (ra sā ya na), not as a title or classification for a specific ritual practice or recipe for pills, but rather to refer to the processes of alchemical transformation of substances within complex ritual "medicinal accomplishment" (sman sgrub) performances which are generally communal. In this case too, pills are produced, of the broader "sacred elixir dharma medicine" (dam rdzas bdud rtsi chos sman) type. This paper will consider a range of the practices, and of substances used in the sacred medicinal compounds.